KYAI HAJI AHMAD SANUSI: BERJUANG DARI PESANTREN HINGGA PARLEMEN - Sulasman, - (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2008)
Kyai Haji Ahmad Sanusi, well known as Ajengan Gunung Puyuh, was a charismatic preacher from Sukabumi and even well known as a preacher in Indonesia. But he was also famous as a politician who fought against the Dutch and the Japanese colonizers. He also had taken a big part in Indonesian history, during the revolutionary era against the colonizers, and there were many more activities he had done for Indonesia. This writing tries to enlighten West Javanese mind and Indonesian in general as well about how Kyai Haji Ahmad Sanusi (KHAS) fought against the colonizers since he was at the pesantren until he was active in the Indonesian parliament.